PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBASIS MIND MAPPING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA - Cindy Septa Sari Br. Sitanggang; Patri Janson Silaban; Antonius Remigius Abi; Juliana; Rumiris Lumbangaol (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the influence of the Problem Based Learning (PBL) model based on Mind Mapping on the critical thinking skills of fourth-grade students at SD Negeri 068007 Simalingkar in the 2024/2025 academic year. This study uses a quantitative method with an experimental design, involving pretests and posttests to measure the improvement in students' critical thinking skills after the implementation of the learning model. The pretest results showed an average score of 60, which falls into the poor category, with the lowest score being 48 and the highest being 76. After the implementation of the Mind Mapping-based PBL model, the posttest results showed a significant improvement, with an average score reaching 88.2 in the very good category and a highest score of 100. The correlation test showed a figure of 0.878, indicating a very strong relationship between the Mind Mapping-based PBL model and students' critical thinking skills. The t-test results in a t-value of 9.702, which is greater than the table value of 2.048, meaning the alternative hypothesis is accepted and the null hypothesis is rejected. Based on the research results, it can be concluded that the application of the Problem Based Learning model based on Mind Mapping has a significant effect on the improvement of students' critical thinking skills. This research provides recommendations to teachers to develop skills in using various learning models, as well as to pay attention to students' learning difficulties in order to provide appropriate guidance. Future researchers are expected to develop this study to further enhance the quality of learning.